When Consumers Love their Brands: A Qualitative Approach for the Investigation on the Nature of this Relationship - Aloisio, Sara (2016)
The marketing literature and the consumer research started to pay attention and particular interest in the consumer-brand relationship. Customers tend to create and develop an emotional connection with some brands, and some researchers tried to explain this phenomenon through the brand love construct. Some studies identified a different number of factors that could explain the love relationship established between an individual and a brand and the consequences of this emotional bond. The methods used in past studies to investigate those results were the combination of qualitative and quantitative approaches. However, the study of this particular concept requires further investigation and the use of new techniques to deeply understand the nature of the feeling of love that consumers experience for a brand. Those, in fact, are the premises that pushed the author of this research to conduct this important investigation. Adopting the Zaltman Metaphor Elicitation Technique (ZMET) on a sample of fifteen participants, this research found five factors that are significant for a consumer to fall in love with a brand: feeling special, connecting and sharing, protection, sexual attraction, and the feeling of empowerment and excitement. This study found few similarities with past academic and practitioner researches, but those connections resulted to have also different interpretations. So, this research helped to enrich the marketing literature in the field of the consumer-brand relationship, especially to identify the nature of the feeling of love that consumers experience for a brand.